The Gislinge Boat Open Source Project: An Old Boat and a New Idea - Tríona Sørensen; Martin Rodevad Dael; Silas Tavs Ravn; Marie Broen; Marie Krogh Nielsen (EXARC Journal)
In 1993, the remains of a wooden boat were uncovered during drainage works north of the village of Gislinge, on the island of Sjælland in Denmark (Gøthche 1995). Now reclaimed agricultural land, the area had once been part of the shallow Lammefjord, itself connected to the Isefjord and the open sea. The boat was remarkably well preserved, and initial features such as the stepped stem and overlapping planking suggested that it may have been Viking Age in date (Gøthche 1995: 186). Later analysis proved the excavators’ first impressions were reasonably accurate; the find was dendrochronologically dated to ca. AD 1130, making it the first significant Danish find of a smaller vessel from the early Middle Ages.